PENERAPAN FUNGSI MANAJEMEN PADA KELOMPOK TANI ASI ENDO DI DESA TEWASEN KECAMATAN AMURANG BARAT KABUPATEN MINAHASA SELATAN - Kivry E. Salmon; Jenny ., Baroleh; Juliana R. Mandei (Sam Ratulangi University, 2017)
The purpose of this research is to know the implementation of management function in Asi Endo Farmer Group in Tewasen Village, Amurang Barat Subdistrict, South Minahasa Regency. The study was conducted from April to June 2017. The data used were primary data obtained from direct interviews with the management and members of farmer groups based on prepared questions list and direct observation or survey in the research site. Data analysis used is descriptive analysis, presented in tabular form, then the resultant data is analyzed by using likert scale. The results showed that the implementation of Asi Endo farmer group management function in Tewasen Village, Amurang Barat subdistrict of South Minahasa Regency covering the function of planning, organizing function, movement function, supervisory function and assessment function, as a whole is in the Very Good category with 82.8% . This means that group members together with group administrators are very good at implementing management functions within the Asi Endo farmer group.*jrm*